Rundt om Arbejdersangbogen fra 1926 - Albris, Josefine (Arbejderhistorie, 2026)
Arbejdersangbogen (the Workers’ Songbook) of 1926 emerged during a transitional period, when the labor movement was shifting from a class-based movement toward a broader popular foundation. The songbook brings together both national and international songs of struggle, as well as national classics, into a single repertoire. This composition points to a central tension: how can a songbook both preserve a tradition of political struggle while also opening toward home, leisure, and the nation? The curation of the songbook shows that it not only continues the historical narrative of the labor movement but actively shapes a broader cultural self-understanding. Through its selections and omissions – along with the exclusion of strike songs – it appears as a cultural-political document that reflects and processes the contemporary tension between class identity and a grounding in the population as a whole.